Integration of Ontological, Epistemological, and Axiological Foundations in Educational Management Research in Indonesia (Case Study: Managerial Practices in Educational Institutions) - Hajar Adhayanti; Yogie Putranto; Lesfandra Lesfandra (Jurnal Info Sains : Informatika dan Sains, 2026)
Educational management research in Indonesia tends to focus on technical and empirical aspects, while the philosophical dimension is often marginalized. This article aims to analyze the integration of ontological, epistemological, and axiological foundations in educational management practices through case studies of educational institutions in Indonesia. Using a qualitative approach based on document analysis and reflection on managerial practices, this article shows that the success of educational management is determined not only by procedural effectiveness, but also by a clear view of the nature of education (ontology), how to acquire and validate managerial knowledge (epistemology), and the values ​​and goals that underlie decision-making (axiology). These conceptual findings emphasize the importance of integrating the philosophy of science as a foundation for developing contextual and sustainable educational management research and practice in Indonesia